PENGARUH PENGGUNAAN BINDER GELATINE UNTUK FINISHING KULIT CAKAR AYAM TERHADAP KETAHANAN GOSOK CAT TUTUP - Sri Sumarni (Politeknik ATK Yogyakarta, 2013)
This research aims to study the use of artificial gelatine binder remainder split cow leather , patent binder instead of the chicken paw skin tersamak ( Tarso metatursus ) to scrub resistance paint .The material used is skin crust chicken scratch using gelatine binder treatment concentration variation on neutralization using 5 % hydrochloric acid , 5 % Acetic Acid and Citric Acid 5 % ie : 2 , 4 , 6 , 8 and 10 % ( w / w ) compared with patent gelatine binder using 3 % . then tested rub resistance ( SNI. 06-1996-1989 ) .Data analysis used a randomized block design or RCBD where the block is wet scrub resistance versus ketahananngosok fabric paint fabric paint dry , with treatments 2,4,6,8 , 10 % artificial gelatine . The results of the research that binders and binders patent artificial showed no real difference ( ns ) . When seen in the results of the research it is best to use artificial binders neutralizing acetic acid 5 % with the use of binders and 4 % 2 % 4 is a good result when compared to using neutralization with 5 % hydrochloric acid and 5 % citric acid and binder patent .